Selecting the Optimal Airfoil for Automotive Rear Wings: Performance Assessment - Maddani , Osama; Etaig , Saleh; Ebrahim, Al-Hadi; AlJhani , Islam (Scientific Journal of University of Benghazi, 2024)
This study investigates the potential performance and safety improvements achievable through the application of inverted airfoils on a BMW 3-series (E36) car. Computational fluid dynamics (CFD) simulations were employed to assess the aerodynamic characteristics of three distinct airfoil designs: NACA 0012, NACA 4412, and Eppler E423. Evaluations were conducted at 0°in freestream and at 14° angles of attack (AOA) when used in the automotive application to analyze the impact on lift and drag forces. The findings revealed unique aerodynamic profiles for each airfoil. The angle of attack for the airfoils in freestream was chosen to be 0 degrees to isolate the effect of the different airfoil shapes on their performance. This allows us to better understand how their performance translates to the automotive application. Considering automotive applications, the Eppler E423 demonstrated superior potential for enhanced acceleration and cornering speeds compared to the other airfoils. The NACA 4412 also displayed comparable performance to the Eppler E423 in these aspects. Overall, the inclusion of an Eppler E423 airfoil positioned as an inverted wing at a 14° AOA emerged as the configuration offering the optimal balance between performance and safety benefits for the BMW 3-series (E36). This research underscores the significant potential of strategically incorporating aerodynamic devices, such as inverted wings, to achieve improvements in both vehicle safety and performance characteristics.